PENGARUH KUALITAS PELAYANAN DAN HARGA DISKON TERHADAP MINAT BELI DI RESTORAN SABOTEN SHOKUDO KECAMATAN KLOJEN KOTA MALANG - renie resha ekawati; Siti Saroh; daris zunaida (LPPM FIA Unisma Malang, 2020)
The problem of service quality in the company continues to grow along with the times. Companies must carry out marketing strategies in order to survive facing competition in this millennial era. The problems in this research are whether the quality of service and discount prices have a positive and significant influence towards the buying interest in Saboten Shokudo restaurant Klojen district, Malang. The purpose of this research are to find out how many influence of variables of service quality and discounted prices of buying interest in the Saboten Shokudo restaurant Klojen district, Malang.The type of this research is descriptive statistical research with quantitative approach. Samples taken in this research were consumers in Saboten Shokudo restaurant, Klojen district, Malang as much as 78 respondents determined by accidental sampling technique. Data collectig techniques used questionnaires have been tested for validity and reliability. Data analysis technique used is multiple linear regression, to test the hypothesis of every independent variable used the t test and to test the hypothesis variable simultaneously used the F test. The results of this research are the variable quality of service and discount prices significantly influence buying interest in Saboten Shokudo restaurant, Klojen district, Malang.